Olam ha-zeh v'olam ha-ba : this world and the world to come in Jewish belief and practice - Greenspoon, Leonard J. (Leonard Jay) (Studies in Jewish civilization ;, 2017)
"Dining on Leviathan. Discoursing with Socrates. Debating the nature of existence in the afterlife. These are among the topics authors address in this wide-ranging account of how Jews have conceptualized the world to come and structured their lives in this world accordingly. The chronological range of these chapters also is impressive. The earliest documents discussed are from Apocryphal literature, including apocalypses, that were composed from 400 BCE to 200 CE. There are creative analyses of rabbinic material and documents from the medieval period through the twentieth century. Evolving ritual and liturgical practices bring readers up to the early twenty-first century. Each of the thirteen authors whose works are brought together in this volume shows historical, cultural, and religious sensitivity both to the unique features of these differing manifestations and to the elements that unite them. For the readers of this volume, which is equally rewarding for general audiences and for specialists, the result is a carefully nuanced, creatively balanced exploration of the breadth of Jewish thought and practice concerning some of the most profound and perplexing issues humans face"--